Absence of significant genetic alterations in the VSX1, SOD1, TIMP3, and LOX genes in Brazilian patients with Keratoconus - Lopes, Alessandro Garcia [UNESP]; de Almeida Jr, Gildásio Castello; Miola, Marcos Paulo; Teixeira, Ronan Marques [UNESP]; Pires, Francielly Camilla Bazilio Laurindo; Miani, Rodolfo Andrade; de Mattos, Luiz Carlos; Brandão, Cinara Cássia; Castiglioni, Lilian [UNESP] (Taylor & Francis, 2021)
Purpose: To identify inherited or acquired mutations in the VSX1, SOD1, TIMP3 and LOX genes from the combined analysis of corneal and blood samples from patients with Keratoconus. Methods: The casuistry was consisted of samples of peripheral blood and corneal epithelium from 35 unrelated patients with Keratoconus who were submitted to corneal crosslink treatment. Also, blood and corneal epithelium samples from 89 non-keratoconic patients were used to compose the control group. Ophthalmologic evaluations included a clinical examination, topography and tomography. DNA samples were extracted from peripheral blood and from corneal epithelium in both groups and all coding regions of the VSX1, SOD1, TIMP3 and LOX genes were amplified by polymerase chain reaction, denatured and subjected to polyacrylamide gel electrophoresis. Mutational screening was performed by single-strand conformation polymorphism and direct DNA sequencing. Results: No pathogenic variant was found in all coding regions of VSX1, SOD1, TIMP3 and LOX genes, we detected only few SNPs (single-nucleotide polymorphisms). Among the polymorphisms stand out three of them, corresponding to the synonymous exchange of amino acids: exon 3 of VSX1 Ala182Ala and exon 3 of TIMP3 His83His and Ser87Ser; in patients with Keratoconus and also in control subjects. All the polymorphisms were found in samples of corneal epithelium and corresponding blood. Conclusion: There is absence of KC pathogenic related to mutations in the VSX1, SOD1, TIMP3 and LOX genes in the studied patients.
Keywords: Cornea; ectasia; genetic polymorphisms; Keratoconus; lysyl oxidase gene; superoxide dismutase 1 gene; TIMP3 gene; visual system homeobox 1 gene